DLTS characterization of proton‐implanted silicon under varying annealing conditions. Issue 11 (4th September 2014) - Laven, J. G.; Jelinek, M.; Job, R.; Schustereder, W.; Schulze, H.‐J.; Rommel, M.; Frey, L.
<x xml:space="preserve">Abstract</x> Deep‐level defects remaining in the upper half of the band‐gap of silicon implanted with protons at fluences and annealing temperatures typically used for proton‐implantation doping are investigated. For proton fluences in the range of several 1013 cm−2 to several 1014 cm−2, a multitude of deep‐level defects remain active in comparatively high concentrations of up to 1013 cm−3 even after anneals at temperatures up to 500 °C. The detected deep‐levels are assigned to known lattice defects on the basis of their electrical characteristics obtained by Fourier‐transform DLTS measurements. Despite the low oxygen content of the float‐zone silicon used, a large number of the detected defects are ascribed to (non‐)hydrogenated vacancy‐oxygen defects. The annealing temperature ranges, in which the deep‐level defects were detected, are shown. Furthermore, the dependencies of the deep‐level defects on the proton fluence and their depth distributions in the implantation profile are investigated.